How to Become God? - Milewska, Monika (Poznańskie Studia Slawistyczne, 2013)
Sanctity is the very essence of political power, which needs its own rituals, myths, and symbols. This sacred nimbus confirms the authority of the ruler, making it unusual, mysterious and – as a result – untouchable. Religion is also the main source of the legitimacy of power, changing rulers into the sons of gods or at least kings „by the grace of God”. The twentieth century brought a new phenomenon: totalitarian personality cult, which is based on archaic beliefs and myths concerning power. Personality cult was a kind of charismatic power described by Max Weber, who considered charisma as strictly personal supernatural gifts of a new ruler. This article focuses on efforts made by the twentieth century dictators in order to create an artificial charisma and to become a living (and ruling) god.